The Cochrane Skin Group: a vanguard for developing and promoting evidence-based dermatology - Reddi, Anand; Prescott, Laura; Doney, Elizabeth; Delamere, Finola; Kollipara, Ramya; Dellavalle, Robert P.; Williams, Hywel C. (Wiley, 2013)
Aim The Cochrane Skin Group (CSG) is part of the international Cochrane Collaboration (http://www.cochrane.org/). The CSG prepares, maintains and disseminates high quality evidence-based summaries on the prevention, diagnosis and treatment of skin diseases. We present a synopsis of the history, scope and priorities of the CSG. In addition, we report outcomes of CSG reviews and critically assess clinical value.